A study to assess the effectiveness of structured teaching program on knowledge regarding good touch and bad touch among children of selected primary school of Kanpur. (International Journal of Food and Nutritional Sciences, 2022)
The study was conducted among the school children in primary school, Kanpur. The main purpose ofthis study was to assess the knowledge level of school children regarding the good touch and bad touch.The sample sizes selected for this study were 76 school children which were selected by non probabilityconvenience sampling technique. The data was collected by using the self structured knowledgequestionnaire. After complete data collection and analysis the results for this study showed that 67%students were having good knowledge and rest 33% students were having poor knowledge regardinggood touch and bad touch. And it also found that there was no significant association between theknowledge score and their demographic variable. Therefore hypothesis H0 was not rejected. Theconclusion of this study shows that there was significant knowledge level among students regarding thegood touch and bad touch.